Alcoholic Fermentation Activators: Bee Pollen Extracts as a New Alternative - Juan Manuel Pérez-González; José Manuel Igartuburu; Víctor Palacios; Pau Sancho-Galán; Ana Jiménez-Cantizano; Antonio Amores-Arrocha (Agronomy)
Searching for natural alternatives to synthetic fermentation activators has led to the study of bee pollen as a natural alcoholic fermentation activator. This study evaluated the potential of different bee pollen extracts (0.25 g/L) as activators in a Palomino Fino grape must. By analysing the composition of each extract, it was possible to identify the specific bee pollen fractions with the highest efficacy for activating alcoholic fermentation. Four extracts were obtained through sequential extraction using various organic solvents of increasing polarity (hexane, acetone, ethanol, and water), and their compositions were characterised. The effect of each extract was evaluated by monitoring the viable yeast populations and fermentation kinetics throughout the alcoholic fermentation process, along with the physicochemical and colour characterisation of the white wines obtained. The bee pollen fraction extracted with hexane, which was rich in long-chain fatty acids, significantly increased the maximum yeast populations and improved the fermentation kinetics. However, the extracts rich in polyphenolic compounds exhibited slower fermentation rates. Based on the obtained results, the lipid fraction of bee pollen extracted with hexane may be responsible for its ability to activate alcoholic fermentation.